2 - The Migration and Informal Market Nexus: A study of Nigerien Forex Traders in Benin City - Oreva Olakpe; Martha Sambe; Rafeeat Aliyu (Africa Development, 2024)
This article attempts to understand how migrant communities in the global South shape and contribute to the establishment and operation of niche sectors and informal markets in receiving states. The article examines the impact that a community of migrants from Niger Republic have had on the foreign exchange market in Benin City, Edo State, Nigeria. The analysis is situated within the postcolonial framework while drawing on sociological frameworks and methodological tools (ethnography). By analysing the narratives of Nigerien migrants in Benin City, this paper unpacks the characteristics of the migrant forex niche, the interaction between the formal and informal forex businesses in the market, as well as the interplay between migrants and locals in the community. We argue that the nexus of intra- African migrations and informal niche markets leads to spatial, political, economic and social transformations that challenge the significance of formal markets and the limitations of undocumented status.